Isolated Infundibular Pulmonary Stenosis in Adult - Rahman, Md Mostafizur; Sunny, Mohammad Samir Azam; Hasan, Md Kamrul; Adhikary, Asit Baran (University Heart Journal, 2018)
Isolated infundibula pulmonary stenosis (UPS) in adult is an uncommon cardiac abnormality. Infundibula pulmonary stenosis leading to right ventricular hypertrophy is a big problem. Early excision of hypertrophied muscular band can overcome this problem. In our case report we have done excision of pulmonary infundibula muscle band of a late case of isolated pulmonary infundibula stenosis. And our patient showed a good response after excision of infundibula muscle band. University Heart Journal Vol. 13, No. 2, July 2017; 65-66